2020
DOI: 10.1177/1558925020908271
|View full text |Cite
|
Sign up to set email alerts
|

Poisson’s ratios of molded pulp materials by digital image correlation method and uniaxial tensile test

Abstract: The mechanical properties of molded pulp materials are the basis of the structural optimum design of molded pulp products. Therefore, the correlations between Poisson’s ratio and fiber structure, molding process, and thickness were found for materials including wood pulp, bamboo pulp, sugarcane pulp, white mixed pulp, black mixed pulp, recycled corrugated board pulp, and recycled newspaper pulp by the uniaxial tensile test and digital image correlation method. The fiber structures of the selected molded pulp m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Meanwhile, the TMP achieved breaking stresses in the range 25 to 27 MPa, and the recycled pulp reached 15 to 18 MPa (apparently with no additional refining having been applied). Hua et al (2020) evaluated the Poisson's ratios and determined the failure mechanisms of molded paper materials by means of digital images correlations and uniaxial tensile testing. They found that the drying of molded pulp under pressure within a mold led to higher Poisson's ratio.…”
Section: Evaluation Of Elastic Modulus and Stretchmentioning
confidence: 99%
“…Meanwhile, the TMP achieved breaking stresses in the range 25 to 27 MPa, and the recycled pulp reached 15 to 18 MPa (apparently with no additional refining having been applied). Hua et al (2020) evaluated the Poisson's ratios and determined the failure mechanisms of molded paper materials by means of digital images correlations and uniaxial tensile testing. They found that the drying of molded pulp under pressure within a mold led to higher Poisson's ratio.…”
Section: Evaluation Of Elastic Modulus and Stretchmentioning
confidence: 99%
“…Many research methods and results on the influence of its structural form [4][5][6] and size [7,8] on impact resistance have been studied in depth. But the performance of molded pulp materials now focused on its uniaxial tensile or compressive properties, and a few studies of Poisson's ratio [9] touched on the multiaxial mechanical behavior of molded pulp products. The research on the multiaxial stress-strain relationship belongs to the blank area.…”
Section: Introductionmentioning
confidence: 99%
“…21 Subsequently, various research groups observed the same fiber microstructure in molded pulp by SEM. [22][23][24] A continuum model at the mesoscale level was used to study the effect of the uneven fiber distribution on the local strain field, 24 which showed that the inhomogeneous density distribution has the most significant effect. These previous studies only observed the fiber network of MPMs and did not apply the data to constitutive modeling of the material.…”
Section: Introductionmentioning
confidence: 99%